2021
DOI: 10.1038/s41419-021-04252-z
|View full text |Cite
|
Sign up to set email alerts
|

ERp29 forms a feedback regulation loop with microRNA-135a-5p and promotes progression of colorectal cancer

Abstract: Expression of endoplasmic reticulum (ER) stress-associated genes is often dysregulated in cancer progression. ER protein 29 (ERp29) is abnormally expressed in many neoplasms and plays an important role in tumorigenesis. Here, we showed ERp29 is a novel target for microRNA-135a-5p (miR-135a-5p) to inhibit the progression of colorectal cancer (CRC); correspondingly, ERp29 acts as an oncoprotein in CRC by promoting proliferation and metastasis of CRC cells, and suppressing apoptosis of the cells. More importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the combined decitabine and PBA treatment repressed the ER stress response genes ERP29 and PDIA3. Importantly, ERP29 is frequently deregulated in cancer and forms a feedback loop with microRNA-135a-5p to promote progression of colorectal cancer [ 69 ], while protein disulfide isomerase family A member 3 (alias ERP57) modulates folding of glycoproteins and stimulates cell proliferation via c-Myc, PLK1 and the AKT pathway [ 70 ]. Moreover, PDIA3 promotes cancer cell proliferation and is associated with poor prognosis in hepatocellular carcinoma [ 71 ], while the helicase HELLS functions in DNA-strand separation and replication repair.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the combined decitabine and PBA treatment repressed the ER stress response genes ERP29 and PDIA3. Importantly, ERP29 is frequently deregulated in cancer and forms a feedback loop with microRNA-135a-5p to promote progression of colorectal cancer [ 69 ], while protein disulfide isomerase family A member 3 (alias ERP57) modulates folding of glycoproteins and stimulates cell proliferation via c-Myc, PLK1 and the AKT pathway [ 70 ]. Moreover, PDIA3 promotes cancer cell proliferation and is associated with poor prognosis in hepatocellular carcinoma [ 71 ], while the helicase HELLS functions in DNA-strand separation and replication repair.…”
Section: Resultsmentioning
confidence: 99%
“…Although a high level of ERp29 expression can inhibit CNV in vivo, the effect of its overexpression on other cells in the eye as well as its safety with respect to visual function still require further research. In addition, ERp29 is highly expressed in various tumor tissues, and some researchers have identified ERp29 as a carcinogenesis-related gene [60,61]. In addition to the upregulation of ERp29 expression in tumor tissues, the expression of ERp29 can also be upregulated after ionizing radiation [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are crucial post-transcriptional regulators in physiological and pathological environments [6]. Studies have shown that miRNA is rapidly degraded by binding to the 3′-untranslated region (3′-UTR) of the target gene to affect the expression of the gene [7]. What is more, miRNAs are stable in tissue specimens, highlighting their underlying utility as prognostic biomarkers in different diseases, such as cardiovascular disease and inflammation [8,9].…”
Section: Introductionmentioning
confidence: 99%